Surface and water column methane (CH4) distribution and sea-to-air flux during ALKOR cruise AL516 - Sonja Gindorf; Dennis Booge; Annette Kock; Hermann W Bange; Christa A Marandino (PANGAEA, 2020)
We developed a purge-and-trap system to measure CH_4 with high accuracy in the surface water and the water column of the Kiel Bight, close to the monthly time series station Boknis Eck. The small-scale variability of CH_4 was investigated from samples taken in the Baltic Sea during the two Alkor cruises AL510 and AL516 in the in early summer and autumn 2018 when two gas exchange experiments (GasEx) were carried out around the Boknis Eck time series station. This station has been sampled for CH_4 on a monthly basis since 2007.During the GasEx cruises, special emphasis was put on the sampling of the upper water column and the mixed layer, with high-resolution sampling to determine potential gas gradients within the mixed layer that are not captured with conventional sampling approaches. Water column CH_4 samples were collected from Niskin bottles mounted to a CTD-water-rosette-sampler, Dinghy samples were collected using an aquarium pump, Underway samples were taken from the ship extquotesingles sea water supply. All samples were filled bubble-free into dark brown 20 mL glass vials by overflowing the approximate threefold volume and crimp-sealed with rubber stoppers and aluminium caps.